Genetically modified porcine split-thickness skin grafts as an alternative to allograft for provision of temporary wound coverage: preliminary characterization. Issue 3 (May 2015) - Barone, Angelo A. Leto; Mastroianni, Melissa; Farkash, Evan A.; Mallard, Christopher; Albritton, Alexander; Torabi, Radbeh; Leonard, David A.; Kurtz, Josef M.; Sachs, David H.; Cetrulo Jr., Curtis L.
Abstract Temporary coverage of severely burned patients with cadaver allograft skin represents an important component of burn care, but is limited by availability and cost. Porcine skin shares many physical properties with human skin, but is susceptible to hyperacute rejection due to preformed antibodies to α-1, 3-galactose (Gal), a carbohydrate on all porcine cells. Our preliminary studies have suggested that skin grafts from α-1, 3-galactosyltransferase knock out (GalT-KO) miniature swine might provide temporary wound coverage comparable to allografts, since GalT-KO swine lack this carbohydrate. To further evaluate this possibility, eight non-human primates received primary autologous, allogeneic, GalT-KO, and GalT + xenogeneic skin grafts. Additionally, secondary grafts were placed to assess whether sensitization would affect the rejection time course of identical-type grafts. We demonstrate that both GalT-KO xenografts and allografts provide temporary coverage of partial- and full-thickness wounds for up to 11 days. In contrast, GalT + xenografts displayed hyperacute rejection, with no signs of vascularization and rapid avulsion from wounds. Furthermore, secondary GalT-KO transplants failed to vascularize, demonstrating that primary graft rejection sensitizes the recipient. We conclude that GalT-KO xenografts may provide temporary coverage of wounds for a duration equivalent to allografts, and thus, could serve as a readily available alternative treatment of severe burns.